Comparison in weight change on breast cancer patients in Hospital Sultanah Nur Zahirah - Zainudin, Nur Anis Syamimi; Sarizan, Ainun Aqilah; Mohd Nizam, Mohammad Na’im (2018)
Background: The society tends to believe and think that people who have undergone chemotherapy session will lose their weight. Many of them trust that ideology with other equivalent side effect, for example like hair loss (alopecia), and lose appetite. Most of the patients that undergo the chemotherapy session in Hospital Sultanah Nur Zahirah are breast cancer patients. Usually the most common chemotherapy protocol that being used by breast cancer patient is FEC protocol, follow up with FEC+Docexacel protocol and Docetaxel alone, according to the staff in oncology department.